Essential of child welfare - Ellis, Rodney A. (Wiley, 2003)
Case planning is one of the fundamental steps in working with dependent children, yet it is also one of the most challenging. Essentials of Child Welfare presents the key information clinical social workers, child advocates, family law attorneys, and other human services personnel need to work successfully with children and families in the child welfare system. Essentials of Child Welfare is packed with step-by-step guidelines for intervening proactively with foster care children and their caretakers. Techniques are presented for handling a number of related topics, including attachment issues, substance abuse, sexual abuse (victim and perpetrator), suicidal ideation, eating disorders, learning disabilities, juvenile delinquency, domestic abuse, and many more. As part of the Essentials of Social Work Practice series, this book offers a concise yet thorough overview of child welfare, numerous tips for best practices, and a prioritized assembly of all the information and techniques that must be at one’s fingertips to practice knowledgeably, effectively, and ethically. Each concise chapter features numerous callout boxes highlighting key concepts, bulleted points, and extensive illustrative material, as well as "Test Yourself" questions that help you gauge and reinforce your grasp of the information covered.